Enoxacin and bis-enoxacin stimulate 4T1 murine breast cancer cells to release extracellular vesicles that inhibit osteoclastogenesis. Issue 1 (December 2018) - Vracar, Taylor; Zuo, Jian; Park, JeongSu; Azer, Demyana; Mikhael, Christy; Holliday, Sophia; Holsey, Dontreyl; Han, Guanghong; VonMoss, Lindsay; Neubert, John; Rody, Wellington; Chan, Edward; et al.
Abstract Enoxacin and its bone-seeking bisphosphonate derivative, bis-enoxacin, have recently captured attention as potential therapeutic agents for the treatment of cancer and bone disease. No differences in growth or survival of 4T1 murine breast cancer cells were detected at a concentration of 50 µM of enoxacin or bis-enoxacin. Growth was perturbed at higher concentrations. Both 50 µM enoxacin and bis-enoxacin stimulated increases in the number of GW/Processing bodies, but there were minimal changes in microRNA levels. Extracellular vesicles (EVs) released from 4T1 cells treated with 50 µM enoxacin or 50 µM bis-enoxacin stimulated proliferation of RAW 264.7 cells, and both significantly inhibited osteoclastogenesis in calcitriol-stimulated mouse marrow. EVs from 4T1 cells treated with enoxacin and bis-enoxacin displayed small reductions in the amount of microRNA (miR)-146a-5p and let-7b-5p. In marked contrast, miR-214-3p, which has been shown to regulate bone remodeling, was increased 22-fold and 30-fold respectively. We conclude that enoxacin and bis-enoxacin trigger the release of EVs from 4T1 cancer cells that inhibit osteoclastogenesis.